Penerapan Model Game-Based Learning Berbantuan Media Tantangan Panca Cilik terhadap Hasil Belajar Siswa pada Materi Pancasila - Wachdaniyah, Achla Inayatul; Nuriyana, Faizatun; Widodo, Susilo Tri; Suryaningtyas, Ariana Dwi (YASIN, 2025)
Although interactive activity-based learning in Pendidikan Pancasila has been widely examined, research that specifically evaluates the effectiveness of Game-Based Learning (GBL) supported by the Tantangan Panca Cilik media remains limited. This study aims to evaluate the effectiveness of GBL in improving Pancasila learning outcomes among fifth-grade elementary school students. A quantitative approach with a simple experimental design was employed, involving 38 students selected through total sampling. Data were collected through achievement tests, observations, and informal interviews, and were analyzed descriptively using frequency percentages. The findings show that GBL supported by the Tantangan Panca Cilik media is effective in enhancing Pancasila learning outcomes, as indicated by the majority of students achieving the “Sangat Baik” (60.5%) and “Baik” (15.8%) categories. These results contribute to the development of constructivist learning theory and broaden the understanding of the use of educational games in Pendidikan Pancasila instruction. The study underscores the importance of game-based learning strategies in creating active and enjoyable learning environments and recommends that teachers integrate innovative media such as Tantangan Panca Cilik into their teaching practice. In addition, this study opens opportunities for further research in other subject areas and with broader samples.